Pattern of Creativity Explanation based-on Executive Functions of the Brain by Mediating Cognitive-Emotional Regulation among High School Students in Tehran - Farahnaz Balverdi; Narges Babakhani (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objectives: Executive functions are a set of basic cognitive processes that control behavior and thoughts and can help improve the creativity and emotion of individuals. The objective of this study was to investigate the pattern of creativity explanation based on the executive functions of the brain by mediating cognitive-emotional adjustment among high school students in Tehran. Materials and Methods: The present study was a descriptive study of structural equation type. The research population consisted of all high school students in Tehran, among whom 250 were selected by cluster random sampling from 22 municipality districts of Tehran. To obtain the data, the Torrance Creative Thinking Test, the Cognitive Critical Control Questionnaire and the Cognitive Ability Test, to measure executive functions, were used. Data were analyzed using Pearson correlation and structural equations via SPSS software version 22 and AMOS software version 22. Results: The mean (SD) age of male students was 16.8 (5.4) and female students 16.6 (5.3). With the increase in executive functions with mean (SD) of 69.1 (13.4), cognitive-emotional self-regulation increased with a mean (SD) 106.8 (16.6), and with increasing cognitive-emotional self-regulation, creativity with mean (SD) 134.6 (12.8) increased. Creativity is also decreased by increasing executive performance. Increased brain's executive functions mediated in increase in cognitive-emotional regulation variables, creativity. Conclusion: The study showed that increased executive functions were associated with cognitive-emotional self-regulation and increased cognitive-emotional self-regulation was associated with increased creativity. Decreased creativity was associated with increased executive performance. Increased brain's executive functions were associated with increased creativity with cognitive-emotional regulation as a mediating factor. DOI: http://doi.org/10.22037/ch.v7i2.24454